Isolation and Characterisation of Microbial DNA from Rain Tree Barks - Mun, Chee Onn (2017)
Most microorganisms present in nature are uncultivable by standard techniques and functions of commensal bacteria remained largely uncovered. Metagenomics assessment to study microbial community on tree barks was not attempted from literature search. In this research, a metagenomics DNA extraction protocol by combining a series of lysis, extraction and purification methods was developed for high quality genomic DNA extraction of cultivable and uncultivable microorganisms present on local rain tree bark. Sodium dodecyle sulphate (SDS)-based extraction method with cetyltrimethyl ammonium bromide (CTAB) as strong DNA extraction buffer was carried out to extract metagenomes from two bark samples, namely orchid-colonised and non-orchid-colonised bark samples, followed by its qualitative (agarose gel electrophoresis) and quantitative (spectrophotometry) assessments. The quality of metagenomics DNA extracted was insufficient where the A260/A280 ratio was in range from 1.47 to 1.81, and low A260/A230 ratio obtained indicated the probability of contamination by humic substances and phenols. The metagenomic DNA was not suitable for cloning due to inability to be restriction digested by HindIII. The metagenomic DNA was accessed for 16S ribosomal RNA (rRNA) polymerase chain reaction (PCR) amplification and the results suggested that the purity of the metagenomics DNA was sufficient for PCR. Amplification results also indicated the presence of bacteria and fungi in high amount on the bark surface. The presence of archaea cannot be indicated due to unspecific amplification and no single band with the expected size was obtained. No difference between non-orchid and orchid-colonised bark samples in terms of amplified rDNA in the range of 8.2 to 14.1 ug, which were sufficient for next generation sequencing (NGS) for rain tree bark metagenomics study, specifically on the ecology of microorganisms on rain tree bark.